15x + 30y = -10....reduce by dividing by 5
3x + 6y = -2...same as first equation...same line ..means infinite solutions
If I understand this question correctly, Diego will pay $1.12 because the 9 rounds the 1 up to a 2.
Answer:
m=2
Step-by-step explanation:
When you put a number into the inverse of a function (f^-1) you get the original number back.
Ex: f^-1(11) = (11-3)/2 = 4
f(4) = 2×4+3 = 11
So, f(-5)=-2
So, when x is -5,
f(x) = -2
f(x)=m(-5)+8
-2=m(-5) + 8
m=2
You know b=-6 and since you know this, you can plug -6 in for b.
This would become 4(-6) + 6 divided by 6.
You can then multiply 4 and -6 together,
-24 + 6 / 6
You can then add -24 and 6 together,
-18/6
You can then divide -18 by 6,
-18/6=-3
-3 is your final answer
Answer: 137... well i think because 180-43= to 137.